Development of Smart Apps Creator Interactive Multimedia Using a Problem-Based Learning Model in Indonesian Language Learning in Elementary Schools - Rahmi, Intan Aulia; Ahmad, Syafri; Sukma, Elfia; Zen , Zelhendri (Journal of Educational Sciences, 2025)
21st-century education requires students to possess critical, collaborative, and creative thinking skills, as well as the ability to optimally utilize information technology. However, classroom practice still shows limited use of technology, and the learning media employed have not actively engaged students. This study aims to develop interactive multimedia using Smart Apps Creator with a Problem-Based Learning (PBL) model that is valid and practical for teaching Indonesian in elementary schools. This study uses the research and development method (Research and Development) using the ADDIE model. Data were collected through observation, interviews, validation sheets, questionnaires, and tests, then analyzed to determine validity and practicality. The results show that content validity reached 95.31%, language validity 98.43%, and media validity 85.52%, all categorized as highly valid. Practicality scores were 97.08% from students and 94.44% from teachers, both categorized as highly practical. Therefore, the Smart Apps Creator interactive multimedia with a Problem-Based Learning model is considered highly valid and practical, making it feasible for use in Indonesian language learning in elementary schools.